KEMAMPUAN PENALARAN STATISTIS SISWA PADA MATERI PENYAJIAN DATA HISTOGRAM MELALUI PEMBELAJARAN PMRI - Nisa, Sholihatun; Zulkardi; Susanti, Ely (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2019)
This research is a descriptive research which aimed to describe students’ statistical reasoning ability of histogram data persentation material through PMRI learning in SMA Negeri 11 Palembang. This subject of this research was XII class containing 40 students. The process of teaching were suited with the principle and chraracteristic of PMRI. The teachnique of collecting the data of this research was written test which contained 4 description question then supported by interviews to obtain additional test data. Based on the result of the research, it was found that students’ statistical reasoning ability of histogram data persentation material through PMRI learning were good with these following details: 8 students were very good category; 11 students were in good category; 9 students were ini enough category, 7 students were in low category, and no student was in very low statistical reasoning ability. Indicator of statistical reasoning that had the highest appereance is organizing and reducing data which is 84,29% . While, indicator of statistical reasoning that had the lowest appereance is representing data which is 29,52%. DOI: 10.22342/jpm.13.1.5460.21-40